(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: Decribe the structural features and anatomical variance of lateral mass ethmoid bone in chronic sinusitis patients. Subjects and methods: Prospective descriptive study in 55 chronic sinusitis patients underwent surgery in National Otorhinolaryngology Hospital from 2013 to 2022. Results: Anterior ethmoidal air cells included three typical types: anterior uncinate cell (96,36%), suprasellar cell (82,7%) and intrasellar cell (100%). Posterior ethmoidal air cells include three typical types: Avante posterior cell (100%), center posterior cell (100%) and recullar posterior cell (85,5%). There were three common anatomical variances, including ethmoidal artery hernia (62,7%), lateral attachment of uncinate process (62,7%), middle turbinate (16,3%), and paradoxical middle turbinate (14,6%). Conclusion: Lateral mass ethmoid bone was divided into two groups of anterior ethmoidal cells and posterior ethmoidal cells. Each group consisted of three large cell types, which were frequently found. Anatomical variations of the uncinate process and anterior ethmoid artery are common.